2017
DOI: 10.5312/wjo.v8.i2.156
|View full text |Cite
|
Sign up to set email alerts
|

Titanium elastic nailing in diaphyseal femoral fractures of children below six years of age

Abstract: AIMTo report the clinical and radiographic results of titanium elastic nail (TEN) in diaphyseal femoral fractures of children below age of six years.METHODSA retrospective analysis of 27 diaphyseal femoral fractures in children younger than six years treated with TEN between 2005 and 2015 was conducted. Patients were immobilized in a cast for 5 wk and the nails were removed from 6 to 12 wk after surgery. Twenty-four cases were clinically and radiographically re-evaluated using the Flynn’s scoring criteria, foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 30 publications
2
12
0
Order By: Relevance
“…Other complications for spica casting Nascimento [20] n = 30 3 (10%) 1 (3.3%) 2 (6.7%) Shemshaki [16] n = 23 3 (13%) 0 (0%) 3 (13%) Hsu [18] n = 25 2 (8%) 2 (8%) 0 (0%) Mehdinasab [15] n = 30 7 (23.3%) 4 (13.3%) 3 (10%) Flynn [19] n = 35 12 (34%) 6 (17%) 6 (17%) Song [21] n = 24 2 (8,3%) 2 (8.3%) 0 (0%) Buechsensuetz [22] n = 29 10 (34%) 10 (34%) 3 (10%) Younis et al [28] n = 20 4 (16.6%) 4 (16.6%) 0 (0%) D'Ollonne [26] n = 14 3 (21.4%) 2 (14.3%) 1 (7.1%) Yandow [27] n = 55 5 (9.1%) 3 (5.5%) 2 (3.6%) Curtis [24] n = 21 10 (48%) 8 (38%) 2 (10%) Henderson [25] n Nascimento [20] n = 30 3 (10%) 2 (6.7%) 1 (3.3%) Shemshaki [16] n = 23 3 (13%) 0 (0%) 3 (13%) Hsu [18] n = 26 3 (11.5%) 3 (11.5%) 0 (0%) Mehdinasab [15] n = 36 6 (16.7%) 6 (16.7%) 0 (0%) Flynn [19] n = 48 10 (21%) 6 (12.5%) 4 (8.3%) Song [21] n = 27 4 (14.8%) 1 (3.7%) 3 (11.1%) Buechsensuetz [22] n = 42 9 (22%) 7 (17%) 2 (5%) Ramo [13] n = 104 17 (16.3%) 9 (8.7%) 8 (7.7%) Ruhallah [7] n = 25 2 (8%) 2 (8%) 0 (0%) Assaghir [11] n = 52 10 (19%) 9 (17%) 1 (2%) Jauquier [9] n = 27 3 (11%) 2 (7.4%) [7] n = 25 4 (17%) 4 (17%) 0 (0%) Assaghir [11] n = 52 20 (38%) 20 (38%) 0 (0%) Jauquier [9] n = 19 2 (10.5%) 2 (10.5%) 0 (0%) Younis et al 2019 [28] n = 24 6 (30%) 6 (30%) 0 (0%) D'Ollonne [26] n = 21 3 (14.3%) 3 (14.3%) 0 (0%) Yandow [27] n = 33 1 (3.0%) 1 (3%) 0 (0%) Curtis [24] n include compartment syndrome and superior mesenteric artery syndrome [34,35]. Intramedullary nailing comes with general risks related to anesthesia and surgery risks like wound infection [7,16,3...…”
Section: Results and Previous Literaturementioning
confidence: 99%
“…Other complications for spica casting Nascimento [20] n = 30 3 (10%) 1 (3.3%) 2 (6.7%) Shemshaki [16] n = 23 3 (13%) 0 (0%) 3 (13%) Hsu [18] n = 25 2 (8%) 2 (8%) 0 (0%) Mehdinasab [15] n = 30 7 (23.3%) 4 (13.3%) 3 (10%) Flynn [19] n = 35 12 (34%) 6 (17%) 6 (17%) Song [21] n = 24 2 (8,3%) 2 (8.3%) 0 (0%) Buechsensuetz [22] n = 29 10 (34%) 10 (34%) 3 (10%) Younis et al [28] n = 20 4 (16.6%) 4 (16.6%) 0 (0%) D'Ollonne [26] n = 14 3 (21.4%) 2 (14.3%) 1 (7.1%) Yandow [27] n = 55 5 (9.1%) 3 (5.5%) 2 (3.6%) Curtis [24] n = 21 10 (48%) 8 (38%) 2 (10%) Henderson [25] n Nascimento [20] n = 30 3 (10%) 2 (6.7%) 1 (3.3%) Shemshaki [16] n = 23 3 (13%) 0 (0%) 3 (13%) Hsu [18] n = 26 3 (11.5%) 3 (11.5%) 0 (0%) Mehdinasab [15] n = 36 6 (16.7%) 6 (16.7%) 0 (0%) Flynn [19] n = 48 10 (21%) 6 (12.5%) 4 (8.3%) Song [21] n = 27 4 (14.8%) 1 (3.7%) 3 (11.1%) Buechsensuetz [22] n = 42 9 (22%) 7 (17%) 2 (5%) Ramo [13] n = 104 17 (16.3%) 9 (8.7%) 8 (7.7%) Ruhallah [7] n = 25 2 (8%) 2 (8%) 0 (0%) Assaghir [11] n = 52 10 (19%) 9 (17%) 1 (2%) Jauquier [9] n = 27 3 (11%) 2 (7.4%) [7] n = 25 4 (17%) 4 (17%) 0 (0%) Assaghir [11] n = 52 20 (38%) 20 (38%) 0 (0%) Jauquier [9] n = 19 2 (10.5%) 2 (10.5%) 0 (0%) Younis et al 2019 [28] n = 24 6 (30%) 6 (30%) 0 (0%) D'Ollonne [26] n = 21 3 (14.3%) 3 (14.3%) 0 (0%) Yandow [27] n = 33 1 (3.0%) 1 (3%) 0 (0%) Curtis [24] n include compartment syndrome and superior mesenteric artery syndrome [34,35]. Intramedullary nailing comes with general risks related to anesthesia and surgery risks like wound infection [7,16,3...…”
Section: Results and Previous Literaturementioning
confidence: 99%
“…Based on their study involving the findings of 30 pediatric patients (their age ranged from 6 to 15 years old) with femoral diaphyseal fractures, Kayaokay et al 12 highlighted that TEN surgery is an effective and easy surgery along with minimal complication. Similarly, in another study on 27 children under the age of 6 who were treated with TEN surgery following the femoral fractures, Donati et al 1 reported that the TEN surgery is safe, mini-invasive, and has high patient satisfaction. In accordance with the previous studies, fracture union occurred in all the patients (6 of them were under 6 years old and 29 of them were between 6 and 15 years old) in our study.…”
Section: Discussionmentioning
confidence: 87%
“…While nonoperative treatment had been the most common choice in the past, pediatric orthopedic surgeons have avoided long-term immobilization in the last 20 years because of the disadvantages such as malunion, limited range of motion, delayed functional return, and long-term hospitalization [7][8][9] . Since titanium elastic nailing surgery allows early mobilization, allows micromotion hence promote fracture healing, does not harm the epiphysis, and has the advantages of easy application, this surgery has become the ideal treatment in the surgical treatment of closed pediatric femoral shaft fractures of all ages 1,10,11 . Based on their study involving the findings of 30 pediatric patients (their age ranged from 6 to 15 years old) with femoral diaphyseal fractures, Kayaokay et al 12 highlighted that TEN surgery is an effective and easy surgery along with minimal complication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the 3-point pressure on the bone, the pre-bent bow shape of the TEN is less likely to back out. In our cohort, the rotational force was resisted with postoperative long arm cast over 4 weeks at the forearm supination position for radial paralleling the ulna, and pre-bent TENs are designed in a hockey stick shape with the nail tip inserted into the radial head for rotational stability [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%